Expression of Mathematical Functions in the Python Programming Language - Alimova Rayhon Abdugaforovna (Genius Journals, 2023)
In this article, we will look at mathematical functions and how they are represented in the python programming language and environment. We will refer to the library of mathematical functions included in the Python programming language, and we will compile programs of several mathematical functions and show the results.
Keywords: Standard functions; math; expression; import